Prospecção mineral de alvos potenciais à ocorrência de enriquecimento supergênico de níquel no Greenstone belt do Morro do Ferro - Faria Júnior, Ilio Rodarte [UNESP] (2015)
Metamafic-ultramafic rocks from Morro do Ferro Greeenstone Belt occur in the southeastern Minas Gerais State, Brazil, between the southwestern border of São Francisco Craton and the Brasília Fold and Thrust Belt. Serpentinized or chloritized ultramafic rocks, as described in Morro do Ferro Greeenstone, have great potential to produce expressive supergenic nickel concentrations under lateritization processes. The enrichment occurs because minerals like olivine and pyroxene have a high capability to incorporate nickel in their crystal structure and have a high weathering susceptibility. Since elements have specific geochemical behavior, the lateritization process leads to the formation of sub-horizontal facies, or zones, with distinct concentrations of major and trace elements. In this work, these characteristics, i.e., chemical and mineralogical zoning, are used to identify potential nickel-bearing supergenic concentrations. Geological, geomorphological, remote sensing (SRTM elevation data and Landsat 7 band compositions) data are used to define spatial distribution of horizontal lateritic facies that are exposed by erosive processes. Mineral spectra information and remote sensing techniques allowed identification of five different lateritic facies. Results are in accordance with mineralogical zoning observed in lateritic profiles developed on mafic-ultramafic rocks under tropical to subtropical conditions. Field observation confirm the occurrence of greenish mottled horizons, formed from the weathering of ultramafic schists. Chemical and mineralogical analyses of these horizons show nickel enrichment up to 350% when compared to the parent rock